2011
DOI: 10.5152/tjh.2011.07
|View full text |Cite
|
Sign up to set email alerts
|

PET CT imaging in extramedullary hematopoiesis and lung cancer surprise in a case with thalassemia intermedia

Abstract: Extramedullary hematopoiesis (EMH) is the production of hematopoietic precursors outside the bone marrow cavity, and it causes mass effects according to its localization. Magnetic resonance imaging (MRI) and/or computed tomography (CT) scans are used most commonly to detect EMH foci. We report herein a case with thalassemia intermedia causing paravertebral mass associated with EMH detected by CT scan. We further evaluated the case with positron emission tomography (PET) CT, and lung cancer, which was not revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…As a result of the findings in the spleen on FDG-PET/CT, the patient underwent uncomplicated splenectomy and was discharged from hospital after 14 days in stable condition. Here the patient achieved double benefit of the splenectomy in treating the infection and potentially reducing future transfusion requirements [1][2][3][4]. Our findings mirror the typical characteristics described in the literature of EMH, and in this case, FDG-PET/CT contributed to the finding of the focus of infection in a male known with beta-thalassemia media [5][6][7][8][9][10][11] (Fig.…”
supporting
confidence: 83%
“…As a result of the findings in the spleen on FDG-PET/CT, the patient underwent uncomplicated splenectomy and was discharged from hospital after 14 days in stable condition. Here the patient achieved double benefit of the splenectomy in treating the infection and potentially reducing future transfusion requirements [1][2][3][4]. Our findings mirror the typical characteristics described in the literature of EMH, and in this case, FDG-PET/CT contributed to the finding of the focus of infection in a male known with beta-thalassemia media [5][6][7][8][9][10][11] (Fig.…”
supporting
confidence: 83%
“…The characteristics of EMH on 18 F-FDG PET/CT have not yet been established, with only 2 cases reported to date (8, 9). There is currently no report regarding 18 F-FDG PET/CT scans of EMH mimicking malignancy in MM.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no report regarding 18 F-FDG PET/CT scans of EMH mimicking malignancy in MM. In one report describ- ing thoracic EMH diagnosed upon 18 F-FDG PET/CT in a thalassemia patient, the authors found a 13-cm paravertebral mass at the posterior-inferior mediastinum with mild FDG avidity (SUV max = 2.5) (8). Another report of a thalassemia patient revealed multiple paravertebral thoracic masses with mild to moderate FDG avidity (SUV max not indicated) (9).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) and thorax computed tomography (CT) scans are the most commonly used diagnostic method for EMH. They appear as lobular masses in the paravertebral region [4]. In diagnosis, PET/CT scan may be useful.…”
Section: Discussionmentioning
confidence: 99%